Phenotypic characterization and clinical outcome in ampullary adenocarcinoma. Issue 1 (2nd May 2016) - Asano, Eisuke; Okano, Keiichi; Oshima, Minoru; Kagawa, Seiko; Kushida, Yoshio; Munekage, Masaya; Hanazaki, Kazuhiro; Watanabe, Jota; Takada, Yasutsugu; Ikemoto, Tetsuya; Shimada, Mitsuo; Suzuki, Yasuyuki; et al.
Abstract : Background: Although various features of ampullary adenocarcinoma have been reported, the impact of genetic alterations and rare subtypes on clinical outcome remains unclear. Methods: We determined the expression of proteins, including MUC1, MUC2, p53, p16, Smad/Dpc4, and β‐catenin, and genetic mutations such as KRAS, BRAF, and GNAS mutations in 69 patients with ampullary adenocarcinoma to clarify their relationships with clinicopathological findings and subtypes. Results: Kaplan–Meier survival analysis indicated that abnormal p53 labeling was significantly associated with a shorter overall survival. MUC1 ‐ positive and MUC2 ‐ negative expressions were significantly associated with lymphatic invasion, pancreatic invasion, lymph node metastasis, and advanced UICC stage. The KRAS mutation was significantly associated with large tumor size and pancreatic invasion. There were 35 intestinal (50%), 15 pancreatobiliary (22%), and 11 mixed subtype (16%) tumors. Patients with the mixed subtype showed significantly poor outcome. The invasiveness of the mixed subtype was similar to that of the pancreatobiliary subtype; moreover, the mixed subtype showed a high incidence of abnormal β‐catenin immunolabeling (73%). Conclusions: Protein expression and genetic mutation are clinically associated with the characteristics of ampullary adenocarcinoma. The mixed subtype may have a distinct tumor nature as compared to other two major subtypes. J. Surg. Oncol. 2016;114:119–127 . © 2016 Wiley Periodicals, Inc.